Linking place attachment and social interaction: towards meaningful public places - Ujang, Norsidah; Kozlowski, Marek; Maulan, Suhardi (Emerald, 2018)
Purpose A public space is a place of significance when it fulfils the human need for social interaction and attachment. However, the scarcity of public spaces poses a challenge to support socialisation for people within a defined social and cultural group. The purpose of this paper is to explore the association between place attachment and social interaction within public spaces in the city centre of Kuala Lumpur, Malaysia.